Penerapan Sanksi Pidana pada Kasus Penganiayaan yang Menyebabkan Kematian - Khairil Fahmi Daulay; Daud D (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Assault resulting in death is a form of crime against the human body and life that carries serious legal implications. This study aims to analyze the application of criminal sanctions against perpetrators of assault resulting in death and to examine the legal considerations taken by judges in imposing such sanctions. The research employs a normative juridical approach by examining primary legal materials, including the Indonesian Criminal Code (KUHP), as well as secondary legal materials such as legal literature and court decisions. The findings indicate that the legal classification of assault resulting in death is primarily regulated under Article 351 paragraph (3) of the Indonesian Criminal Code (KUHP), where the element of intent (dolus) is directed solely at the act of assault, while the resulting death is considered an unintended consequence (culpa). In determining criminal sanctions, judges take into account both juridical considerations, including the fulfillment of statutory elements and the sufficiency of evidence, and non-juridical considerations, such as the offender's background and aggravating and mitigating circumstances. Fair law enforcement is expected not only to emphasize retributive justice but also to consider justice for the victim's family.